Development of an ultrathin liquid sheet target for laser ion acceleration at high repetition rates in the kilohertz range - M. Füle; A. P. Kovács; T. Gilinger; M. Karnok; P. Gaál; S. Figul; G. Marowsky; K. Osvay (High Power Laser Science and Engineering, 2024)
A colliding microjet liquid sheet target system was developed and tested for pairs of round nozzles of 10, 11 and 18 μm in diameter. The sheet’s position stability was found to be better than a few micrometers. Upon interaction with 50 mJ laser pulses, the 18 μm jet has a resonance amplitude of 16 μm at a repetition rate of 33 Hz, while towards 100 Hz it converges to 10 μm for all nozzles. A white-light interferometric system was developed to measure the liquid sheet thickness in the target chamber both in air and in vacuum, with a measurement range of 182 nm–1 μm and an accuracy of ±3%. The overall shape and 3D shape of the sheet follow the Hasson–Peck model in air. In vacuum versus air, the sheet gradually loses 10% of its thickness, so the thinnest sheet achieved was below 200 nm at a vacuum level of 10–4 mbar, and remained stable for several hours of operation.